Characterization of the complete chloroplast genome sequence of Chinese endemic species of Nouelia insignis (Hyalideae, Asteraceae) and its phylogenetic implications. Issue 4 (3rd April 2022) - Liu, Xiaofeng; Han, Maoyun; Chen, Jia; Zhang, Xun; Chen, Zhiyu; Tang, Yi; Qu, Tianmeng; Huang, Chunping; Yu, Shuhua; Fu, Zhixi
Abstract: This study was the first report complete chloroplast genome of Nouelia insignis (Asteraceae, Hyalideae), the large shrubs to small trees endemic to China. The circular whole cp genome of N. insignis was 151, 524 bp in length, containing a large single-copy (LSC) region of 83, 145 bp and a small single-copy (SSC) region of 18, 261 bp. These two regions were separated by a pair of inverted repeat regions (IRa and IRb), each of them 25, 060 bp in length. A total of 135 functional genes were encoded, consisting of 89 protein-coding genes, 38 tRNA genes, and eight rRNA genes. The overall GC content of the chloroplast genome sequence was 37.8%, and the GC contents of the LSC, SSC, and IR regions were 35.9, 31.5, and 43.2%, respectively. The phylogenetic analysis by the Bayesian analysis showed that the species of N. insignis was sister group with Gerbera jamesonii by strong support values, and thus was closely related to members of subfamilies of Cichorioideae and Pertyoideae. These results will be useful for the future studies of Asteraceae in the worldwide.